Flexible Connection Elastomeric Rubber as a Pounding Resisting Element between Two Adjacent Buildings - Lase, Yuskar; Oetomo, James Jatmiko (UI Scholars Hub, 2011)
Flexible Connection Elastomeric Rubber as a Pounding Resisting Element between Two Adjacent Buildings To solve pounding problem of two adjacent buildings, structural designer usually employs a dilatation between the structures or make the two structures as a monolith structure. Other alternative is by using an elastomeric rubber as a pounding resisting element between the two structures. Effectiveness in applying elastomeric rubber component as flexible connection of two adjacent structures is the main focus of this paper. Various simulations such as structure models, earthquake excitations and openings in gap element are studied. Observation of maximum structural responses will be performed for structure model with elastomeric rubber in comparison with (1) monolith structure model and (2) structure model with rigid element (steel element). Simulation results show that application of elastomeric rubber component to prevent structures from pounding problem provides advantages especially in reducing internal forces in the shorter building. However, it slightly increases displacement of both structures.